2010
DOI: 10.1007/s00431-010-1155-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin preparations affect hyponatremia in Kawasaki disease

Abstract: Hyponatremia frequently occurs in Kawasaki disease (KD). The aim of this study was to investigate the effect of Na content of the intravenous immunoglobulin (IVIG) preparation on serum Na levels in KD. Seventy-eight subjects, of whom 27 had hyponatremia, were split up into two groups: group A receiving IVIG preparations containing high Na (0.9%) and group B receiving IVIG preparations containing trace Na. While the data before IVIG therapy revealed no significant differences in the median serum Na between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It should be noted that the sodium content of intravenous immunoglobulin (IVIG) that can be used for Kawasaki disease in Japan can range from trace to 154 mEq/L. Kaneko et al report that when children with hyponatremia caused by Kawasaki disease receive an IVIG containing little sodium, the improvement is delayed even if the hyponatremia does not worsen . Hyponatremia can cause brain edema and other factors, so patients with Kawasaki disease complicated by hyponatremia should consider using IVIG containing high concentration (154 mEq/L) of sodium.…”
mentioning
confidence: 99%
“…It should be noted that the sodium content of intravenous immunoglobulin (IVIG) that can be used for Kawasaki disease in Japan can range from trace to 154 mEq/L. Kaneko et al report that when children with hyponatremia caused by Kawasaki disease receive an IVIG containing little sodium, the improvement is delayed even if the hyponatremia does not worsen . Hyponatremia can cause brain edema and other factors, so patients with Kawasaki disease complicated by hyponatremia should consider using IVIG containing high concentration (154 mEq/L) of sodium.…”
mentioning
confidence: 99%
“…The present study showed that the high-Na IVIG preparation was associated with reductions in the proportions of CAAs and IVIG resistance for KD patients in the acute phase, using a large nationwide inpatient database in Japan. A previous study on patients with KD in the acute phase showed no signi cant difference in the proportion of CAAs between the high-Na IVIG group (n=48) and low-Na IVIG group (n=30) [14]. The previous study may have failed to show a signi cant difference between the two groups because of its small sample size.…”
Section: Discussionmentioning
confidence: 79%
“…After IVIG therapy, the levels of these inflammatory cytokines change depending on the response to therapy: they decline in responders and do not decline in non‐responders. Hence, serum Na level improves immediately in responders, but the hyponatremia is prolonged in non‐responders . Accordingly, serum Na may be indicative of the trends of the inflammatory cytokines during the acute stage of KD, and prolonged hyponatremia after IVIG therapy may indicate IVIG unresponsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, serum Na level improves immediately in responders, but the hyponatremia is prolonged in non-responders. 21,24,25 Accordingly, serum Na may be indicative of the trends of the inflammatory cytokines during the acute stage of KD, and prolonged hyponatremia after IVIG therapy may indicate IVIG unresponsiveness.…”
Section: Hyponatremia In Acute Kdmentioning
confidence: 99%